The influence of childhood socioeconomic status on Chinese female university students’ fertility intentions: the chain mediating effect of parental emotional warmth and subjective well-being - Hua, Junli; Mao, Leiyan; Liao, Huiyun; Li, Yihui; Zhang, Haoyao; Liu, Wanqi; Tang, Hong (Frontiers in Psychology, 2025)
ObjectiveThis study examines the impact of childhood socioeconomic status on Chinese female university students’ fertility intentions and the mechanisms by which parental emotional warmth and subjective well-being play a role.MethodA total of 590 female university students at Gannan Medical University completed questionnaires. The childhood socioeconomic status scale, the simplified parenting styles questionnaire, the index of well-being, and fertility intention scale were used to measure childhood socioeconomic status, parental emotional warmth, subjective well-being, and Chinese female university students’ fertility intentions.Results(1) Childhood socioeconomic status, parental emotional warmth, subjective well-being, and fertility intentions among Chinese female university students were significantly positively correlated; (2) Childhood socioeconomic status significantly and positively predicted the fertility intentions of Chinese female university students; (3) Fathers’ emotional warmth and subjective well-being played separate mediating roles in the influence of childhood socioeconomic status on the fertility intentions of Chinese female university students; and (4) Parental emotional warmth and subjective well-being were chain mediators of the effect of childhood socioeconomic status on Chinese female university students’ fertility intentions.ConclusionThe results indicate that childhood socioeconomic status influences the fertility intentions of Chinese female university students both directly and indirectly. The indirect effect occurs through a chain mediation process involving parental emotional warmth and subjective well-being.